Cellulose synthase interactive1- and microtubule-dependent cell wall architecture is required for acid growth in Arabidopsis hypocotyls. (4th February 2020) - Xin, Xiaoran; Lei, Lei; Zheng, Yunzhen; Zhang, Tian; Pingali, Sai Venkatesh; O'Neill, Hugh; Cosgrove, Daniel J; Li, Shundai; Gu, Ying
Abstract : We observed a correlation between acid growth and crossed-polylamellate cell walls which was dependent on CSI1 and microtubules. This is significant for re-evaluating current models of cell morphogenesis. Abstract: Auxin-induced cell elongation relies in part on the acidification of the cell wall, a process known as acid growth that presumably triggers expansin-mediated wall loosening via altered interactions between cellulose microfibrils. Cellulose microfibrils are a major determinant for anisotropic growth and they provide the scaffold for cell wall assembly. Little is known about how acid growth depends on cell wall architecture. To explore the relationship between acid growth-mediated cell elongation and plant cell wall architecture, two mutants ( jia1-1 and csi1-3 ) that are defective in cellulose biosynthesis and cellulose microfibril organization were analyzed. The study revealed that cell elongation is dependent on CSI1-mediated cell wall architecture but not on the overall crystalline cellulose content. We observed a correlation between loss of crossed-polylamellate walls and loss of auxin- and fusicoccin-induced cell growth in csi1-3 . Furthermore, induced loss of crossed-polylamellate walls via disruption of cortical microtubules mimics the effect of csi1 in acid growth. We hypothesize that CSI1- and microtubule-dependent crossed-polylamellate walls are required for acid growth in Arabidopsis hypocotyls.